1967
DOI: 10.1084/jem.126.2.305
|View full text |Cite
|
Sign up to set email alerts
|

Cells as Antigen Carriers and as Immunoglobulin Producers

Abstract: Tolerance induction and antibody formation appear to be alternative consequences of exposure to antigen. The decision between the alternatives depends, on the one hand, on the dose (1, 2), structure (3), and molecular weight (4, 5) of the antigen and, on the other, on the age, species, and immunological status of the recipient. While some of the factors which cause tolerance in adult animals have been explored in detail, little is known about the conditions which promote antibody formation after neonatal expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

1969
1969
1976
1976

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 35 publications
1
1
1
Order By: Relevance
“…They therefore concluded that antibody formation is a property of the donor cells transferred to the irradiated recipient. Our results using the rabbits are consistent with those of Mitchell and Miller (25,26) and Chou et al (21) in that they unequivocally demonstrate the host origin of the antibody-forming cell. Plaque formation was inhibited when spleen cells of irradiated recipients injected with allogeneic normal bone marrow and sheep erythrocytes were incubated with antiserum directed to the recipient allotype prior to the addition of complement to the plates.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…They therefore concluded that antibody formation is a property of the donor cells transferred to the irradiated recipient. Our results using the rabbits are consistent with those of Mitchell and Miller (25,26) and Chou et al (21) in that they unequivocally demonstrate the host origin of the antibody-forming cell. Plaque formation was inhibited when spleen cells of irradiated recipients injected with allogeneic normal bone marrow and sheep erythrocytes were incubated with antiserum directed to the recipient allotype prior to the addition of complement to the plates.…”
Section: Discussionsupporting
confidence: 82%
“…One possible explanation for the lack of correlation between our results, those of Mitchell and Miller (25,26), and Chou et al (21), on the one hand, and those of Harris et al (27)(28)(29)(30)(31), on the other, may be related to the type of antigen used. The latter have used the Shigella as antigen and have assumed that the immune response induced with it is a primary one.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation